Meneliti Situs-Situs Awal Peradaban di Pulau Bengkalis - - Khairiah; - Jarir (STAIN Bengkalis, 2018)
Bengkalis is an island between the inland Sumatera (the upstream of Siak River) and the port of Malacca (past trading center). On geographical side, Bengkalis is the most strategic place used as a trading center. So don’t be surprised if there are many ancient objects found in Bengkalis River such as gold coins, ceramics, bullets and others. The result of tracing historical objects, evidently, in Kuala Bengkalis River is the beginning of the Bengkalis city. Furthermore, after being controlled by the Netherlands (through Tratat Siak), the construction of Bengkalis city was moved by the Netherlands to the center of the city at this time.___________________Keywords: Things, Historical, Bengkalis